6PPD and 6PPDQ embryonic exposure induced distinct developmental neurotoxicity in zebrafish - Liang Yang; Xiangqi Lu; Dongliang Pan; Yusong Zhang; Yi Zheng; He Mei; Bo Yang; Da Sun; Qiong Li; Jian Lin; Jiangfei Chen (Ecotoxicology and Environmental Safety)
The ecological risks of tire antioxidant 6PPD and its transformed metabolite 6PPD-quinone (6PPDQ) have received high attention. The present study evaluated the developmental neurotoxicity and potential mechanisms under 6PPD or 6PPDQ embryonic exposures in zebrafish. Our findings revealed that embryonic exposure to both compounds suppressed larval locomotion during dark periods, while only 6PPD significantly reduced the larval light stimulus sensitivity and phototactic response. Following recovery to juvenile stages, pretreated fish exhibited heightened anxiety and reduced sociability for both chemicals, aggression was exclusively occurred in 6PPDQ, shoaling pattern was tighter in 6PPDQ but looser in 6PPD. Both compounds elevated larval cell death and oxidative stress while inhibiting cranial development, with 6PPD increasing and 6PPDQ decreasing inter-ocular distance. Transgenic strain analyses demonstrated that 6PPD markedly activated Gfap and Olig2 expression in the eye-brain axis region, whereas 6PPDQ specifically enhanced Olig2 expression in brain region. Retinal müller cells (labeled by Gfap) and cone cell patterns were disrupted exclusively by 6PPD, as was the fan-like lens arrangement visualized via Cms1 mitochondrial labeling. Molecular analyses aligned with these observations that both compounds altered neural development genes (sox2, nrxn2a, rab33a), while 6PPD specifically dysregulated ocular development genes (cyp26a, rlbp1b, rdh5). Conversely, 6PPDQ exhibited stronger activation of xenobiotic metabolism and redox activity genes (cyp1a, gstp1, prdx1, p4ha1a) and uniquely upregulated intestinal immune (ccr9a) and potassium channel (kcnj1a.3) genes expression. In silico affinity analysis corroborated these distinctions, showing 6PPD’s preferential binding to CYP26A and 6PPDQ’s stronger interaction with CYP1A. These findings collectively suggest that 6PPD and 6PPDQ induce divergent neurotoxicity pathways of eye-brain axis disruption and gut-brain communication perturbation, respectively, which likely drive their compound-specific behavioral effects.